Iosanthus crypticus (Hyacinthaceae subfam. Urgineoideae), a new species from Namibia - Martínez-Azorín, Mario; Eichhoff, Anka; Crespo, Manuel B.; Rügheimer, Silke (Phytotaxa, 2026)
Field exploration in the farm Vergenoeg in northern Namibia revealed an undescribed species of Iosanthus, which shares the diagnostic characters of the genus, but differs from the other species by distinct morphological characters. Accordingly, we here describe Iosanthus crypticus, based on plants with minute overall plant size, filiform, greyish leaves, spurred bracts, minute stellate flowers, free tepals, free stamens with filiform filaments and ovoid ovary with narrowly columnar style, among other features. We provide a complete morphological description of the new species as well as data on ecology, distribution and relationships with related species.